(untitled) (Mugda Medical College Journal, 2025)
Rasmussen’s aneurysm is a rare but life-threatening complication of pulmonary tuberculosis, characterized by a pseudoaneurysm of a branch of the pulmonary artery adjacent to a tuberculous cavity. We report a case of a young male presenting with massive hemoptysis due to Rasmussen’s aneurysm, emphasizing the diagnostic challenges and management strategies. He visited our hospital for hemoptysis due to pulmonary aneurysm diagnosed by contrast computed tomography (CT) and angiography. He was diagnosed with pulmonary tuberculosis by detection of Mycobacterium Tuberculosis by rapid molecular test (GeneXpert MTB/RIF) in bronchoalveolar lavage. The causes of hemoptysis due to pulmonary tuberculosis are known to be Rasmussen aneurysm, in which the blood vessel wall adjacent to the lung cavity is thinned to form an aneurysm, or bleeding from the bronchial artery. In this case, it was considered that the inflammation caused by pulmonary tuberculosis spread directly to the pulmonary artery and formed a pulmonary aneurysm. Similar cases have been rarely reported in our country. Mugda Med Coll J. 2025; 8(2): 164-166